Past, current, and potential treatments for cryptosporidiosis in humans and farm animals: A comprehensive review - Khan, Shahbaz M.; Witola, William H. (Frontiers in Cellular and Infection Microbiology, 2023)
The intracellular protozoan parasite of the genus Cryptosporidium is among the leading causes of waterborne diarrheal disease outbreaks throughout the world. The parasite is transmitted by ingestion of infective oocysts that are highly stable in the environment and resistant to almost all conventional disinfection methods and water treatments. Control of the parasite infection is exceedingly difficult due to the excretion of large numbers of oocysts in the feces of infected individuals that contaminate the environment and serve as a source of infection for susceptible hosts including humans and animals. Drug development against the parasite is challenging owing to its limited genetic tractability, absence of conventional drug targets, unique intracellular location within the host, and the paucity of robust cell culture platforms for continuous parasite propagation. Despite the high prevalence of the parasite, the only US Food and Drug Administration (FDA)-approved treatment of Cryptosporidium infections is nitazoxanide, which has shown moderate efficacy in immunocompetent patients. More importantly, no effective therapeutic drugs are available for treating severe, potentially life-threatening cryptosporidiosis in immunodeficient patients, young children, and neonatal livestock. Thus, safe, inexpensive, and efficacious drugs are urgently required to reduce the ever-increasing global cryptosporidiosis burden especially in low-resource countries. Several compounds have been tested for both in vitro and in vivo efficacy against the disease. However, to date, only a few experimental compounds have been subjected to clinical trials in natural hosts, and among those none have proven efficacious. This review provides an overview of the past and present anti-Cryptosporidium pharmacotherapy in humans and agricultural animals. Herein, we also highlight the progress made in the field over the last few years and discuss the different strategies employed for discovery and development of effective prospective treatments for cryptosporidiosis.